Towards sustainable farming: Feasibility study into energy recovery from bio-waste on a small-scale dairy farm. (10th February 2018) - Purdy, Andrew; Pathare, Pankaj B.; Wang, Yaodong; Roskilly, Anthony Paul; Huang, Ye
Abstract: Anaerobic digestion (AD) of farm biomass is growing importance as it offers environmental benefits and the biogas produced from AD which can be used as fuel for co-generation of heat and electricity. The study aimed to explore the viability of energy recovery from bio-waste on a small-scale dairy farm to produce biogas using AD and the gas used as biofuel to fuel a combined heat and power (CHP) which generated electrical power and heat for the farm. The AD and the CHP system was designed and simulated using ECLIPSE software. Various ages of cow manure were sampled, analysed and used as an AD feedstock and it was found that as cow manure aged the amount biogas produced from anaerobic digestion was decreased; a reduction in biogas production of 5.76% was found over two months, and in the subsequent two months the reduction rate was found to accelerate, leading to a 16.92% reduction after four months. It was found that 1 t fresh manure as the feedstock produced 58.6 m 3 of biogas. That means cow manure should be used as an AD feedstock as soon as possible, as carbon lost in the form of methane (CH4 ) occurs naturally in the atmosphere, accelerating over time. The rate of CH4 emission is increased by 3 fold (i.e. 21, 196 kg per year) if the annual manure mass is left uncovered for four month. Early insertion of fresh manure into an anaerobic digester can significantly increase biogas production and subsequently reduce emissions of CH4, which has a global warming potential (GWP) of twenty-five times that of carbon dioxide (CO2 ). The simulation results indicated that enough energy can be recovered from the quantity of cow manure available on the farm to provide the electrical and heating energy demands of the farmyard and the attached dwellings, thus creating a sustainable farming system. In combination with the environmental benefits, it was determined that a substantial annual revenue could be generated from utility bill savings and current favourable incentive rates available to promote renewable energy technologies in farming industry in the UK. Highlights: Biogas production was decreased with manure age. Cow manure should be used as an AD feedstock as soon as possible. Enough energy can be recovered from the quantity of cow manure for sustainable farming. Total power output was reduced by 13.87% after four months.